ENHANCING ENGLISH VOCABULARY MASTERY THROUGH CHAIN CARD GAMES FOR JUNIOR HIGH SCHOOL STUDENTS AT SMPN 7 MEDAN - Waruwu, Rista Jane Dwistaryan (English Language Teaching Prima Journal (ELT), 2024)
This study aims to evaluate the effectiveness of Chain Card Game strategy in improving vocabulary of eighth grade students at SMP Negeri 7 Medan. The research method used Classroom Action Research (PTK). Classroom Action Research (CAR) with three cycles: Pre-cycle, cycle1, and cycle2 to assess the impact of this strategy on students participation and performance. Data was collected through observation, grade scores, and documentaion. The analysis of data demonstrated a notable enhancement in the students vocabulary abilities following the implementation of the chain card game strategy. These findings reinforce the significance of interactive and game-based learning methodologies in enhancing English language proficiency. Further investigation could elucidate the long-term consequences of employing this strategy on students language abilities.